Ballistic interval - Gagey, Pierre-Marie (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
We lack a stabilometric parameter that gives us information about the reaction speed of the upright postural control system. This article provides a way to extract this information from the diffusion analysis where it is present. No clinical application of this new parameter can be provided. It is only observed that it is redundant with no conventional parameter.